A natural history of ladybird beetles - Majerus, M. E. N. (Cambridge University Press, 2016)
The Coccinellidae are a family of beetles, known variously as ladybirds or ladybugs. In Britain alone, some 46 species belong to the Coccinellidae family, although only 26 of these are recognisably ladybirds. Composed largely of Professor Michael Majerus' lifetime work, and updated by two leading experts in the field, this book reveals intriguing insights into ladybird biology from a global perspective. The popularity of this insect group has been captured through societal and cultural considerations, coupled with detailed descriptions of complex scientific processes, to provide a comprehensive and accessible overview of these charismatic insects. Bringing together many studies on ladybirds, this book has been organised into themes, ranging from anatomy and physiology to ecology and evolution. This book is suitable for interested amateur enthusiasts, and researchers involved with ladybirds, entomology and biological control.